Differences in Psychological Resilience among Adolescents in Earthquake-Affected Areas based on Gender, Parenting Styles, and Psychosocial Problems - Eka Budiarto; Astriana Astriana; Nur Intan Kusuma (Fakultas Ilmu-ilmu Kesehatan, 2026)
Resilience is crucial for adolescents, a vulnerable group that may suffer adverse effects from earthquakes. A large number of adolescents continue to experience stress and trauma as a result of such events. This study aimed to determine the differences in psychological resilience among adolescents based on gender, parenting style, and psychosocial problems. This quantitative research employed a cross-sectional design with a sample size of 232 participants. Simple random sampling was used, with the inclusion criteria targeting adolescents who resided in the earthquake-affected area, directly experienced the earthquake, and exhibited psychological impacts such as anxiety, fear, and excessive sadness. Adolescent resilience was measured using a modified version of the Brief Resilience Scale questionnaire. Data were analyzed using a three-way ANOVA with a 2x2x2 factorial design. The results showed that the average resilience score was 19.25 out of a maximum possible score of 30, suggesting that adolescent resilience remains considerably below its potential maximum. Psychological resilience among adolescents in earthquake-affected areas was not significantly influenced by gender (p = 0.381), parenting style (p = 0.607), or psychosocial problems experienced during the earthquake (p = 0.331). Therefore, adolescent resilience appears unaffected by these factors. However, further research is warranted to explore other potential influences, including coping mechanisms, decision-making skills, and stress management.